THE LEGALITY OF EX-ISIS CITIZENSHIP FROM INDONESIA IN IRAQ AND SYRIA - Pulung Widhi Hari Hananto (Diponegoro Law Review, 2021)
After the death of the supreme commander of the Islamic State of Iraq and Syria (ISIS), Abu Bakar Al Baghdadi, marked the end of ISIS's legitimacy and hegemony in the Arabian Peninsula. The incident actually led to a new polemic related to the fate of combatants or sympathizers whose support the ISIS (Foreign Terrorist Fighter). With the defeat of ISIS, many FTF are trapped unable to return to their home/ origin countries. On the other side, the sentiment of the country of origin has arisen to not accept its citizens back and lead to revocation of citizenship status. As one of the donor countries for ISIS member, the Government of Indonesia is faced with serious problems regarding the legality of citizenship status and the threat of radical ideology. The dilemmatic attitude to revoke Indonesian citizenship or to repatriate the Ex-ISIS becomes a matter of climax. The issue of this article to centralize and highlight the legality toward the ex-ISIS citizenship from Indonesia in Iraq and Syria. In addition, this article also to give the perspective and elaboration in matter of consequences to repatriate those former ISIS or to withdraw their citizenship.  The results of the study of this article are criticized and also analyze the legality of citizenship of ex ISIS member from Indonesia.